Line-shape broadening of an autoionizing state in helium at high XUV intensity. (28th January 2022) - Aufleger, Lennart; Friebel, Patrick; Rupprecht, Patrick; Magunia, Alexander; Ding, Thomas; Rebholz, Marc; Hartmann, Maximilian; Ott, Christian; Pfeifer, Thomas
Abstract: We study the interaction of intense extreme ultraviolet (XUV) light with the 2s2p doubly excited state in helium. In addition to previously understood energy-level and phase shifts, high XUV intensities may lead to other absorption-line-shape distortions. Here, we report on experimental transient-absorption spectroscopy results on the 2s2p line-width modification in helium in intense stochastic XUV fields. A few-level-model simulation is realized to investigate the origins of this effect. We find that the line-shape broadening is connected to the strong coupling of the ground state to the 2s2p doubly excited state which is embedded in the ionization continuum. As the broadening takes place for intensities lower than for other strong-coupling processes, e.g. observed asymmetry changes of the absorption profile, this signature can be identified already in an intermediate intensity regime. These findings are in general relevant for resonant inner-shell transitions in nonlinear experiments with XUV and x-ray photon energies at high intensity.